Transcranial magnetic stimulation and amyloid markers in mild cognitive impairment: impact on diagnostic confidence and diagnostic accuracy - Alessandro Padovani (Alzheimer’s Research & Therapy, 2019)
Abstract Background The development of diagnostic tools capable of accurately identifying the pathophysiology of mild cognitive impairment (MCI) has become a crucial target considering the claim that disease-modifying treatments should be administered as early as possible in the disease course. Transcranial magnetic stimulation (TMS) protocols have demonstrated analytical validity in discriminating different forms of dementia; however, its value in daily clinical practice in MCI subjects is still unknown. Objective To evaluate the clinical value of TMS compared to amyloid markers on diagnostic confidence and accuracy in MCI subjects, considering clinicians’ expertise. Methods One hundred seven MCI subjects were included and classified as MCI-Alzheimer disease (MCI-AD), MCI-frontotemporal dementia (MCI-FTD), MCI-dementia with Lewy bodies (MCI-DLB), or MCI-other in a three-step process based on (i) demographic, clinical, and neuropsychological evaluation (clinical work-up); (ii) clinical work-up PLUS amyloidosis markers or clinical work-up PLUS TMS measures; and (iii) clinical work-up PLUS both markers. Two blinded neurologists with different clinical expertise were asked to express a diagnostic confidence for each MCI subgroup, and ROC curve analyses were performed at each step. Results The addition of TMS markers to clinical work-up significantly increased the diagnostic confidence for MCI-AD (p = 0.003), MCI-FTD (p = 0.044), and MCI-DLB (p = 0.033) compared to clinical work-up alone, but not for MCI-other (p > 0.05). No significant differences between the add-on effect of TMS and the add-on effect of amyloid markers to clinical work-up were observed (p > 0.732), while the diagnostic confidence further increased when both markers were available. The greater the clinical expertise, the greater the flexibility in considering alternative diagnosis, and the greater the ability to modify diagnostic confidence with TMS and amyloid markers. Conclusions TMS in addition to routine clinical assessment in MCI subjects has a significant effect on diagnostic accuracy and confidence, comparable to well-established biomarkers of amyloidosis.